Procesos de profesionalización docente en Argentina: la experiencia de EnFoCo ETP - Drolas, Ana (2022)
The article that is presented constitutes the result of a research process carried out between 2019 and 2020, for the National Institute of Technical Education (INET), around the territorial deployment of the Program “In Continuous Training Professional Technical Education (EnFoCo ETP)”. The Program brings together the offer of courses, postgraduate degrees and learning communities of the INET that allows ETP teachers to face integrated training actions and build professional careers. The central objective of the article is to give an account of the experience of the teachers who received training in 2018, taking into account the transformations that they promote in the processes of professionalization of the activity and their know-how and the impact on daily practices in the classrooms. . The research was carried out through a combination of qualitative and quantitative methodological strategies, conducting interviews with trained ETP teachers during 2018, and administering 489 surveys to trained teachers. The research has revealed, on the one hand, the central importance that professionalizing training processes related to the innovation of content teaching have for technical education teachers and, on the other, the strong impact that these processes have. in all aspects that concern the professional teaching work, especially in relation to educational contexts and classroom spaces.